Acid alpha-glucosidase in Malaysians: population studies and the occurrence of a new variant - Teng, Yao Sheng; Tan, Soon Guan (Karger, 1979)
Acid alpha-glucosidase from the placenta was electrophoretically surveyed in a total of 633 Malaysians, 236 of Malay, 261 of Chinese and 136 of Indian ancestries. A new variant, alpha-glucosidase 3-1 was observed in 1 Malay and 3 Indians. A polymorphism for this enzyme was observed among Indians, but in Chinese and Malays variants are rare. Phenotype 2-1 was observed once in a Chinese and once in a Malay.